2022
DOI: 10.1155/2022/4661929
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Prognostic Model Based on Cuproptosis-Related lncRNA Signatures in Pancreatic Cancer

Abstract: Aim. The aim of this study is to identify cuproptosis-related lncRNAs and construct a prognostic model for pancreatic cancer patients for clinical use. Methods. The expression profile of lncRNAs was downloaded from The Cancer Genome Atlas database, and cuproptosis-related lncRNAs were identified. The prognostic cuproptosis-related lncRNAs were obtained and used to establish and validate a prognostic risk score model in pancreatic cancer. Results. In total, 181 cuproptosis-related lncRNAs were obtained. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…One of them was the prognostic protective factor lncRNA AC091057.1, which was associated with 68.87% of mRNAs in our study. The expression of AC091057.1 was experimentally verified and was consistent with the results of a pancreatic cancer study indicating it as a protective factor in cancer 36 . In a diffuse large B cell lymphoma (DLBCL) study, the knockdown of ARRDC1-AS1 exacerbated proliferation, inhibited apoptosis, and promoted invasion and migration 37 .…”
Section: Discussionsupporting
confidence: 84%
“…One of them was the prognostic protective factor lncRNA AC091057.1, which was associated with 68.87% of mRNAs in our study. The expression of AC091057.1 was experimentally verified and was consistent with the results of a pancreatic cancer study indicating it as a protective factor in cancer 36 . In a diffuse large B cell lymphoma (DLBCL) study, the knockdown of ARRDC1-AS1 exacerbated proliferation, inhibited apoptosis, and promoted invasion and migration 37 .…”
Section: Discussionsupporting
confidence: 84%
“…4 D). [ 23 , 24 ] Kaplan–Meier analysis confirmed that prognosis was improved in the low-risk group compared with the high-risk group in the training, testing and all cohorts ( P < .05) (Fig. 4 E–G).…”
Section: Resultsmentioning
confidence: 72%
“…were identi ed as lncRNAs associated with cuproptosis, pyroptosis, and ferroptosis, respectively, and showed promising prognostic evaluation characteristics [29][30][31]. Previous research has shown that TDRKH-AS1 promotes tumorigenesis by activating the Wnt pathway in colorectal cancer, and its high expression is associated with poor prognosis in colorectal cancer patients [32].…”
Section: Discussionmentioning
confidence: 99%